Important aspects on beef-cross-dairy breeding related to reproduction and the traits of calves: beef x dairy crossbreeding - Tsiligianni, SA; Ligda, C; Souglis, E; Kazlari, Z; Krystallidou, E; Tsiligianni, Th (Journal of the Hellenic Veterinary Medical Society, 2025)
Crossbreeding between beef sires and dairy dams is not a new concept; it is one of the first practices used on dairy herds. However, the need to raise the milk yield from dairy cows leads to strict selection of dairy genetics and, therefore to a drop in fertility of the cows and to the profit from selling calves. Generally, in dairy farms calves produced, that are not used for replacement animals, are usually sold to fattening units. Due to growth restriction and poor carcass quality of these purebred dairy calves, it is important to reintroduce the beef x dairy crossbreeding to dairy farms for producing more valuable calves. To accomplish the most economic gain from the breeding strategy for crossbreeding, reproductive indices such as conception rate, gestation length, calving difficulty and calf mortality of the beef x dairy crossbreeding animals should be taken into consideration, as well as beef sire’s genetics transmitted ability. Moreover, important factors for beef-cross-dairy calf production are the feed intake and the quality of the carcass as well as some visual characteristics containing weight at birth, coat color, polledness and docility. Lastly, understanding the dairy farmers’ attitude to sire selection and the consumers’ meat preferences could provide valuable information about improving the efficiency of this breeding strategy. In conclusion, beef x dairy crossbreeding could increase meat production especially in countries in need, although more research is needed about synchronization protocols for Artificial Insemination with beef or sexed beef semen to dairy cows.